2021
DOI: 10.18632/aging.203048
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG8 promotes TNF-α expression by sponging miR-454-3p in bone-invasive pituitary adenomas

Abstract: There are few studies on the mechanism of pituitary adenoma (PA) destroying bone. The current study aimed to investigate the role of MEG8/miR-454-3p/TNF-α in bone-invasive pituitary adenomas (BIPAs). In this study, we report that lncRNA MEG8 and TNF-α are upregulated in BIPA tissues while miR-454-3p is downregulated, which is associated with poor progression-free survival (PFS). Functional assays revealed the role of up-regulated MEG8 and down-regulated miR-454-3p in promoting bone destruction. Mechanistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…LncRNAs perform these functions through different mechanisms, including acting as competing endogenous RNAs (ceRNAs) that sponge miRNAs or proteins [ 70 ], promoting or inhibiting long-range chromatin interactions [ 71 , 72 ], acting as molecular scaffolds for guiding chromatin-modifying enzymes [ 73 , 74 , 75 ], and even functioning through the behavior of transcription itself [ 64 , 76 ]. Given the important roles of lncRNAs in the regulation of epigenetic processes, the dysregulation of lncRNAs is implicated in many human diseases [ 9 , 77 , 78 , 79 ]. In addition, increasing studies have shown that lncRNA is involved in the progression, proliferation, apoptosis, autophagy, and metastasis of PA.…”
Section: Lncrna and Pamentioning
confidence: 99%
“…LncRNAs perform these functions through different mechanisms, including acting as competing endogenous RNAs (ceRNAs) that sponge miRNAs or proteins [ 70 ], promoting or inhibiting long-range chromatin interactions [ 71 , 72 ], acting as molecular scaffolds for guiding chromatin-modifying enzymes [ 73 , 74 , 75 ], and even functioning through the behavior of transcription itself [ 64 , 76 ]. Given the important roles of lncRNAs in the regulation of epigenetic processes, the dysregulation of lncRNAs is implicated in many human diseases [ 9 , 77 , 78 , 79 ]. In addition, increasing studies have shown that lncRNA is involved in the progression, proliferation, apoptosis, autophagy, and metastasis of PA.…”
Section: Lncrna and Pamentioning
confidence: 99%
“…MEG8 silencing has considerably decreased tumor growth and burden in animal models of lung cancer [ 8 ]. This lncRNA has a similar effect bone-invasive pituitary adenomas [ 12 ].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Moreover, MEG8 has been shown to participate in the progression of bone-invasive pituitary adenoma through sponging miR-454-3p and increasing TNF-α expression [ 12 ]. Similarly, expression of MEG8 has been found to be elevated in Wilms tumor cells, parallel with up-regulation of CRK and down-regulation of miR-23a-3p.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xue and Ge [ 9 ] identified differentially expressed lncRNAs in PAs and revealed the key lncRNAs associated with the progression of PAs. Moreover, Guo et al [ 10 ] showed that some lncRNAs were associated with the recurrence of nonfunctioning PAs, whereas Zhu et al [ 11 ] demonstrated that the increased expression levels of the lncRNA maternally expressed 8 promoted bone destruction in bone-invasive PAs by regulating miR-454-3p/tumor necrosis factor (TNF)- α axis. Thus, exploring the expression patterns of lncRNAs in IPAs might confirm the existence of novel potential biomarkers for the diagnosis of IPAs.…”
Section: Introductionmentioning
confidence: 99%